The Effectiveness of Red Onion Compress Therapy and Virgin Coconut Oil (VCO) on Infant Body Temperature Regulation Post-DPT Immunization in a Holistic Care Approach - Wahyuni,; Yofa, Indra; Lalita, Elisabeth MF; Fajrin, Irmasanti; Pratiwi, Dian; Purwandari, Atik (Jurnal Midwifery, 2025)
Introduction Fever is one of the most common side effects of DPT immunization in infants, often causing concern among parents. Data from Puskesmas Remboken in 2023 showed that 32.6% of infants experienced Post-Immunization Adverse Events (KIPI), with fever being the most frequent at 29.5%, followed by injection site pain (8.3%), swelling (0.97%), and other reactions (0.57%). Onion compresses are a safe, natural alternative for reducing fever because the compounds they contain help lower body temperature through heat transfer. This study aims to analyze the effectiveness of a combination of red onion and Virgin Coconut Oil (VCO) compresses in reducing fever in infants after DPT immunization at Puskesmas Remboken, Minahasa Regency. Method the research uses a quasi-experimental design with a one-group pretest-posttest approach. The study involved 33 infants selected using accidental sampling based on inclusion and exclusion criteria. Data analysis was conducted using the paired samples t-test and the experiment was conducted for ± 30 days. Result showed that the t-test yielded a p-value of 0.000 (< 0.05), indicating that the combination of red onion and VCO compresses was effective in reducing infant body temperature. Conclusion this combination therapy is an effective, safe, and easily applicable non-pharmacological method for managing fever in infants after DPT immunization. It also has the potential to reduce dependence on antipyretics and improve the quality of infant care.